Enhancing Law Enforcement Efficiency Through Integrated Smart Policing Systems - Setiadi Setiadi (Jurnal Puruhita, 2025)
Smart policing has emerged as a transformative approach to modern law enforcement, leveraging digital technologies, real-time analytics, and interconnected platforms to improve public safety outcomes. This study examines how integrated smart policing systems—comprising IoT sensors, predictive analytics, digital evidence platforms, and automated surveillance networks—reshape police operations in urban environments. Using a mixed-methods design, the research analyzes operational data from three metropolitan areas using smart policing frameworks, supplemented by interviews with 46 police officers, IT specialists, and community stakeholders. Quantitative findings demonstrate a 28% improvement in emergency response times and a 34% increase in crime detection accuracy following the deployment of smart policing tools. Qualitative insights highlight enhanced situational awareness but also emphasize challenges related to data overload, technical interoperability, privacy concerns, and the need for sustained training. The study concludes that smart policing can significantly strengthen law enforcement efficiency when supported by robust governance, ethical data management, and collaborative partnerships. This research contributes to the field of policing studies by providing a comprehensive understanding of how intelligent technologies can be responsibly integrated into daily police operations to build safer communities.